Impact of the associated cation on chloride binding of Portland cement paste. (February 2015) - De Weerdt, K.; Colombo, A.; Coppola, L.; Justnes, H.; Geiker, M.R.
Abstract: Well hydrated cement paste was exposed to MgCl2, CaCl2 and NaCl solutions at 20 °C. The chloride binding isotherms for free chloride concentrations ranging up to 1.5 mol/l were determined experimentally. More chlorides were found to be bound when the associated cation was Mg 2 + or Ca 2 + compared to Na + . The chloride binding capacity of the paste appeared to be related to the pH of the exposure solution. In order to explain the cation dependency of the chloride binding a selection of samples was investigated in detail using experimental techniques such as TG, XRD and SEM–EDS to identify the phases binding the chlorides. The experimentally obtained data were compared with the calculations of a thermodynamic model, GEMS. It was concluded that the measured change in chloride binding depending on the cation was mainly governed by the pH of the exposure solution and thereby the binding capacity of the C-S-H.